PENILAIAN KINERJA MANAJEMEN BANK SYARIAH GUNA MENINGKATKAN KUALITAS PELAYANAN TERHADAP NASABAH DENGAN INTEGRASI DIMENSI MODEL CARTER DAN FUZZY SERVQUAL (Studi Kasus pada BNI Syariah Kantor Cabang Surabaya) - Abdul Djalal (Faculty of Industrial Technology Universitas Islam Indonesia, 2014)
Carter model is a quality service dimension developed by Parasuraman et al to measures service quality which covers Assurance, Reliability, Tangible, Empathy and Responsiveness. The research subject was a syariah company, therefore Compliance dimension is exercised. The instruments applied to measure service quality is questioner in Linkert scale and distributed to costumer. Due to the subjectivity contained in received questioner answers, Fuzzy is utilized to transform it into a quantitative value as an input for Servqual. Thus, servqual is applied to calculate the gap between customer expectations and perceptions of the service offered. By practicing Cartesian diagram, the attributes need to be addressed were attained. The largest gap is in the attribute called “Promised service time” in Reliability dimension with 0.556.